2017
DOI: 10.1371/journal.pone.0173863
|View full text |Cite
|
Sign up to set email alerts
|

Community health worker perspectives on a new primary health care initiative in the Eastern Cape of South Africa

Abstract: BackgroundIn 2010, South Africa’s National Department of Health launched a national primary health care (PHC) initiative to strengthen health promotion, disease prevention, and early disease detection. The strategy, called Re-engineering Primary Health Care (rPHC), aims to provide a preventive and health-promoting community-based PHC model. A key component of rPHC is the use of community-based outreach teams staffed by generalist community health workers (CHWs).MethodsWe conducted focus group discussions and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 22 publications
4
82
0
Order By: Relevance
“…In addition, this study revealed that CHWs are not well accepted in communities. Austin-Evelyn advised that monitoring clients' temperature, blood pressure and weight would enhance CHWs' acceptance in communities [22]. According to him, many members of the community are currently buying and using such screening tools, yet they are not trained, which means that CHWs who have undergone some training would use the screening tools more accurately than the general members of the community [22].…”
Section: The Knowledge Level Of Chws Regarding Their Roles Within Thementioning
confidence: 99%
“…In addition, this study revealed that CHWs are not well accepted in communities. Austin-Evelyn advised that monitoring clients' temperature, blood pressure and weight would enhance CHWs' acceptance in communities [22]. According to him, many members of the community are currently buying and using such screening tools, yet they are not trained, which means that CHWs who have undergone some training would use the screening tools more accurately than the general members of the community [22].…”
Section: The Knowledge Level Of Chws Regarding Their Roles Within Thementioning
confidence: 99%
“…[24] In the absence of such support, CHWs reverted to dispensing shorter-acting methods. [26] CHWs in SA, especially at 'primary healthcare re-engineering' sites, [27] and HIV lay counsellors -already adept at 'task shifting' -could play an important role in implant services through demand creation, conducting pre-insertion counselling around LARCs and providing follow-up support.…”
Section: Fy 2015 Fy 2016 Fy 2017mentioning
confidence: 99%
“…They are employed to mitigate the ongoing professional health workforce shortages in South Africa [2,3]. In addition, they facilitate linkage between communities most in need and PHC facilities, thereby increasing access to basic health services and contributing to improved health [2,3,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Their involvement in active case nding contributes towards the reduced transmission of TB in communities [25]. CHWs conduct systematic household contact TB investigation (SHCI) and refer undiagnosed individuals for clinical evaluation and treatment, trace patients lost to follow-up, and also provide basic behavioural and treatment adherence counselling [7,[9][10][11]. This study sought to understand the dimensions that underly CHWs' motivation to perform SHCI, to ascertain the level of their motivation, and to establish the determinants of their motivation.…”
Section: Introductionmentioning
confidence: 99%